Why Non-Human Rights?. Issue 2 (3rd May 2020) - Gruber, Malte-Christian
Abstract: The common belief in the absolute justifiability and universal validity of human rights still confronts its own powerlessness today in the face of worldwide humanitarian catastrophes. Despite all of the recurring statements about the global protection of their human rights, the voices of the people affected remain unheard, and their legal position resembles a state of rights-deprivation and "bare life". The legitimacy of these human living beings not yet protected by law cannot be established by the anthropocentric rhetoric of human rights ideologues. Instead, it requires the inclusion of associations of humans and things, of non-human living beings, and even of future generations. This is precisely where the chances of a re-humanization of the law lie, based on a posthuman "right to rights."